A nonzero gap two-dimensional carbon allotrope from porous graphene - Brunetto, Gustavo; Santos, Bruno I.; Autreto, Pedro A. S.; Machado, Leonadro D.; Dos Santos, Ricardo P. B. [UNESP]; Galvao, Douglas S. (Springer Nature, 2012)
Graphene has been one of the hottest topics in materials science in the last years. Because of its special electronic properties graphene is considered one of the most promising materials for future electronics. However, in its pristine form graphene is a gapless semiconductor, which poses some limitations to its use in some transistor electronics. Many approaches have been tried to create, in a controlled way, a gap in graphene. These approaches have obtained limited successes. Recently, hydrogenated graphene-like structures, the so-called porous graphene, have been synthesized. In this work we show, based on ab initio quantum molecular dynamics calculations, that porous graphene dehydrogenation can lead to a spontaneous formation of a nonzero gap two-dimensional carbon allotrope, called biphenylene carbon (BC). Besides exhibiting an intrinsic nonzero gap value, BC also presents well delocalized frontier orbitals, suggestive of a structure with high electronic mobility. Possible synthetic routes to obtain BC from porous graphene are addressed. © 2012 Materials Research Society.
Keywords: Ab initio; Biphenylene; Carbon allotropes; Electronic mobility; Frontier orbitals; Gap values; Quantum molecular dynamics; Spontaneous formation; Synthetic routes; Calculations; Electronic properties; Molecular dynamics; Two dimensional; Graphene